THE EFFECT OF SALES PROMOTION AND SHOP ATMOSPHERE ON IMPULSIVE PURCHASES IN TONG HIEN SEMARANG - Septian Deico T; Agus Hermani DS (Penerbit Jurnal Indonesia, 2021)
The appearance and rapid growth of some newer and fresher retails in Semarang, force consumer on deciding the right market to buy a product. This adverse situation lead more problems for the older retail to maintain their position as the central market in Semarang. As one of the oldest retail in Semarang, Tong Hien has been struggling to improve sales overtime. This caused by consumer didn’t have the urge to buy a product aside from what their planned. Therefore, Tong Hien Semarang need to improve marketing strategy to increase their income by stimulate an impulse for consumer to buy more product. This research is being conducted in Tong Hien Semarang to discover the effect of Impulsive buying in Tong Hien Semarang. Thisstype of researchsiskexplanatorysresearch. Thessampling method in this research is nonprobability sampling by purposive sampling. this research is using a google form and spread questionnaire as an instrument to collect data. There are 100 respondents in this research with such experience of buying product in Tong Hien Semarang as a sample. The data analysis that used is simple linear regression. The research concludes that Sales Promotion and Store Atmosphere has significant effects on Impulsive Buying in Tong Hien Semarang.